Antimicrobial efficacy of Cecropin A (1–7)- Melittin and Lactoferricin (17–30) against multi-drug resistant Salmonella Enteritidis. (October 2020) - Gourkhede, Diksha P.; Bhoomika, Sirsant; Pathak, Richa; Yadav, Jay Prakash; Nishanth, Dani; Vergis, Jess; Malik, S.V.S.; Barbuddhe, S.B.; Rawool, D.B.
Abstract: The present study evaluated intracellular antibacterial efficacy of two short-chain cationic antimicrobial peptides (AMPs) namely, Cecropin A (1–7)-Melittin and lactoferricin (17–30) against three field strains of multi-drug resistant Salmonella Enteritidis. Initially, antimicrobial ability of both the AMPs was evaluated for their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against multi-drug resistant S. Enteritidis strains. Besides, the AMPs were evaluated for its in vitro stability (high-end temperatures, proteases, physiological concentrations of cationic salts and pH) and safety (haemolytic assay in sheep erythrocytes; cytotoxicity assay in murine macrophage RAW 264.7 cell line and human epithelioma HEp-2 cell line and beneficial gut lactobacilli). Later, a time-kill assay was performed to assess the intracellular antibacterial activity of Cecropin A (1–7)-Melittin and lactoferricin (17–30) against multi-drug resistant S . Enteritidis in RAW 264.7 and HEp-2 cells. The observed MBC values of Cecropin A (1–7)-Melittin and lactoferricin (17–30) against multi-drug resistant S . Enteritidis (128 μM; 256 μM) were generally twice or four-fold greater than the MIC values (64 μM). Further, both the AMPs were found variably stable after exposure at high-end temperatures (70 °C and 90 °C), protease treatment (trypsin, proteinase K, lysozyme), higher concentration of physiological salts (150 mM NaCl and 2 mM MgCl2 ) and hydrogen ion concentrations (pH 4.0 to 8.0). Both the AMPs were found non-haemolytic on sheep erythrocytes, revealed minimal cytotoxicity in RAW 264.7 and HEp-2 cells, and was tested safe against beneficial gut lactobacilli ( L . acidophilus and L . rhamnosus ). Intracellular bacteriostatic effect with both cationic AMPs against multi-drug resistant S . Enteritidis was evident in RAW 264.7 cells; however, in both the cell lines, the significant bactericidal effect was not observed ( P  > 0.05) with both cationic AMPs understudy against multi-drug resistant S . Enteritidis. Based on the results of the present study, both the cationic AMPs understudy may not be useful for the intracellular elimination of multi-drug resistant S . Enteritidis; hence, further studies such as conjugation of these AMPs with either cell-penetrating peptides (CPP) and/or nanoparticles (NPs) are warranted. Highlights: Intracellular efficacy of two AMPs was explored against MDR- Salmonella Enteritidis. In vitro, both AMPs, CAMA and lactoferricin (17-30) were found stable and safe. Significant intracellular clearance of MDR- S . Enteritidis was not evident with both AMPs. Conjugation studies with either CPP and/or nanoparticles are warranted for both AMPs.